SISTEM KONTROL SMART HOME RADIO FREQUENCY IDENTIFICATION (RFID) ARDUINO UNO - Baharuddin, Andi Rakhmat (Patria Artha Technological Journal, 2024)
Smart home using voice command technology is the best solution in overcoming problems in turning on and off household appliances such as light, fan and water pump so the busy user can run effectively and efficiently, especially for people with disabilities and this smart home also use radio frequency identification (RFID) technology so user can open the door by using an ID card. This research consists of the identification of needs, needs analysis, flowchart programs, block diagrams, system planning, design design, tool assembly, making miniature smart homes, testing tools and collecting data from the test results. Testing on this system uses the black box testing method which prioritizes testing the functional requirements of the assembled system. The results of the test show that the system can work in accordance with its functions and objectives, namely the voice command application can control 12V LED lights and fans up to a distance of 10 meters or more and the automatic door on this smart home can function properly